W.W. Thomson, A Digest of the Acts of Assembly Relating to and the General Ordinances of the City of Pittsburgh 496 (1893) - (:unkn) unknown (My University, 1893)
§ 5, Pt. 3: Prohibited carry of firearms, shooting or throwing of stones, or setting snares within the limits of the park or within one hundred yards thereof.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE